Peranan Advokat Dalam Pendampingan Hukum E-Court dan Dampak Teknologi Terhadap Strategi Litigasi Pada Maskar Indonesia - Muhammad Rifqi Naufal; Ahmad Khoiruddin; Andi Ardiyan Mustakim; Novi Fitriani (Hukum, 2025)
This study aims to provide a deeper analysis of data collection techniques in scientific writing. In conducting research, data collection is a crucial step in obtaining the necessary information. Appropriate data collection techniques and valid research instruments play a crucial role in producing accurate and reliable data. The method used in compiling this scientific paper is descriptive with a qualitative approach. The type of research employed is library research. The results of this study include: First, legal aid is a free legal service provided to the underprivileged to fulfill human rights, covering state administrative, civil, and criminal cases. Based on Law Number 16 of 2011, aid recipients are those with economic limitations, and services are provided free of charge. Second, the implementation of e-Court at the Sumber Religious Court is considered effective in facilitating public access to litigation, especially during the pandemic. This system includes online trials (e-Litigation), electronic payments (e-Payment), and digital file management, saving costs and time, and reducing extortion. This ensures that the data obtained is sufficient and focused enough to make a meaningful contribution to the research.